Sustained immunogenicity of bivalent protein COVID-19 vaccine SCTV01C against antigen matched and mismatched variants - Guiqiang Wang; Kexin Zhao; Xiuli Zhao; Yimin Cui; Peng He; Tianzuo Zhang; Yanchao Wang; Rui Shi; Yanhua Li; Qian Wang; Yanping Ren; Zhisong Chen; et al. (Expert Review of Vaccines)
Background The development of bivalent or multivalent vaccines offers a promising strategy for combating SARS-CoV-2 mutations.Research design and methods In this phase 2 trial, conducted from 1 December 2021, to 25 July 2023, 392 unvaccinated adults aged ≥18 years were randomized to receive a primary series of two doses and a booster dose of SCTV01C, a bivalent protein SARS-CoV-2 vaccine.Results Geometric mean titers (GMTs) of neutralizing antibodies (nAb) against live Alpha, Beta, Delta, and Omicron showed 85.4-, 100.0-, 32.1-, and 9.8-fold increase from baseline on 28 days, and 49.4-, 55.3-, 5.7-fold increase against live Alpha, Beta, and Omicron on 90 days after primary series. At Day 28 and Day 90 following the booster dose, GMTs of nAb against Beta, BA.2 and BA.5 variants showed 12.1- and 8.8-, 13.8- and 7.1-, 18.7-, and 11.9-fold of increase from baseline, respectively. Reactogenicity was generally mild, with one adverse event of special interest (AESI) and 9 ≥Grade 3 treatment-related adverse events (TRAEs); all recovered within 3 days.Conclusions SCTV01C, when administered as both a primary series and a booster vaccination, exhibited encouraging sustained immunogenicity against both antigen-matched and antigen-mismatched variants, with no significant safety concerns.Clinical trial registration www.clinicaltrials.gov identifier is NCT05148091.